If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9(x + 9) + -2(2x + -8) = 11 Reorder the terms: 9(9 + x) + -2(2x + -8) = 11 (9 * 9 + x * 9) + -2(2x + -8) = 11 (81 + 9x) + -2(2x + -8) = 11 Reorder the terms: 81 + 9x + -2(-8 + 2x) = 11 81 + 9x + (-8 * -2 + 2x * -2) = 11 81 + 9x + (16 + -4x) = 11 Reorder the terms: 81 + 16 + 9x + -4x = 11 Combine like terms: 81 + 16 = 97 97 + 9x + -4x = 11 Combine like terms: 9x + -4x = 5x 97 + 5x = 11 Solving 97 + 5x = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-97' to each side of the equation. 97 + -97 + 5x = 11 + -97 Combine like terms: 97 + -97 = 0 0 + 5x = 11 + -97 5x = 11 + -97 Combine like terms: 11 + -97 = -86 5x = -86 Divide each side by '5'. x = -17.2 Simplifying x = -17.2
| 2x+10x=-8 | | -40-2n=-8(8+n) | | 6-.75x=3 | | X-9y=-19 | | 6n+2-4=4 | | 3*8+7+4d-1=58 | | (x-3y)(x+3y)=36 | | Y=(7/2)^X | | -5x-4x=18 | | p/10=-4/5 | | 8x+4-17x=58 | | 17-x=39 | | 5(x-3)+4=3x-2 | | a-(-26)=88 | | 6k^2+17k+12=0 | | .06x^2+.31x+4=10 | | (X+2)+(2X-1)=4X-7 | | 4-4x-3x=-10 | | m-(-50)=-1 | | 8(2g+-5)= | | 8(2g-5)g= | | f(-x)=3x^2+2x+8 | | V=(2/3)(3.14)r^3 | | 3a^2/2x4/9a | | 4x-3(x+2y)=y+1 | | (2a^2+3y)= | | 2-10=20 | | 2(7x+3)=-3 | | 5m^2-20=2m^3-8m | | 5x^2=-220 | | 9y-8-5y+7=0 | | 15x+18y= |